Evaluation Of Two Different Doses of Injection Lignocaine in Attenuating Hemodynamic and Airway Responses to Extubation –A Clinical Study - Bagade, Ashwini; Mohan, Akshita; Lakra, Anshu Priyanka; Ankita, Ankita; Kushwaha, Jitendra; Choudhary, Rahul (Journal of Neonatal Surgery, 2025)
Background and Aim: Tracheal extubation at the end of anaesthesia induces exaggerated haemodynamic and airway reflexes. Tracheal extubation accompanied by marked sympatho-adrenal response leading to tachycardia, hypertension,coughing,bucking,laryngospasm and branchospasm. Lignocaine is being used for many years to suppress the reflex responses to laryngoscopy and intubation but only a few studies have been carried out to suppress reflex response to extubation. The objective of our study is to evaluate and compare the effectiveness of two different intravenous lignocaine doses (1 mg/kg and 1.5 mg/kg) in attenuating haemodynamic responses and airway reflexes during extubation. Material and Method: This prospective, comparative study was carried out at GMC Bhopal following approval from the Institutional Ethics Committee. A total of 75 patients, aged between 20 and 50 years and classified as ASA physical status I and II, undergoing various surgeries under general anaesthesia were enrolled. The patients were randomly allocated into three groups of 25 each: Group I (control group) received normal saline, Group II received lignocaine 1 mg/kg, and Group III received lignocaine 1.5 mg/kg. Data analysis was performed using IBM SPSS Statistics software, applying the unpaired t-test. A p-value of less than 0.05 was considered statistically significant. Result: In the control group (Group I), a significant increase in heart rate (HR), systolic blood pressure (SBP), and mean arterial pressure (MAP) was observed throughout the study period, with moderate and severe cough occurring in 44% and 32% of patients, respectively. The attenuation of diastolic blood pressure and mean arterial pressure was significantly better with lignocaine 1.5 mg/kg (Group III) compared to the other groups (P<0.001). No significant difference in systolic blood pressure was noted between patients who received 1 mg/kg and 1.5 mg/kg of lignocaine. A significant reduction in heart rate was observed in Group III compared to Group II. Complete suppression of post-extubation cough was achieved in patients administered 1.5 mg/kg of lignocaine. Conclusion: Based on our study findings, we conclude that lignocaine at a dose of 1.5 mg/kg is significantly more effective than 1 mg/kg in attenuating Hemodynamic responses and Cough reflex during and following extubation